Programming languages and systems : 27th European Symposium on Programming, ESOP 2018, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings /: 27th European Symposium on Programming, ESOP 2018, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings. (2018) - Unknown
No abstract available